Testing delay in an environment of low COVID-19 prevalence: A qualitative study of testing behaviour amongst symptomatic South Australians - Emma Tonkin; Heath Pillen; Samantha B. Meyer; Paul R. Ward; Clare Beard; Barbara Toson; John Coveney; Julie Henderson; Trevor Webb; Dean McCullum; Annabelle M. Wilson (Elsevier, 2022)
Introduction: South Australia has to date (October 2021) been highly successful in maintaining an aggressive suppression strategy for the management of the COVID-19 pandemic. However, continued success of this strategy is dependent on ongoing testing by people with symptoms of COVID-19 to identify, trace and quarantine emergent cases as soon as possible. This study sought to explore community members' decisions about having COVID-19 testing in an environment of low prevalence, specifically exploring their decision-making related to symptoms. Materials and methods: This study drew on a qualitative case study design, involving five focus groups, conducted in May 2021, with 29 individuals who had experienced COVID-19-like symptoms since the commencement of testing in South Australia. Participants detailed their last COVID-19-like illness episode and described their decision-making regarding testing. Data collection methods and analysis were theoretically informed by the capability, opportunity, and motivation behaviour (COM-B) model. Findings: Participants' belief that COVID-19 symptoms would be 'unusual', severe, and persistent caused them to either reject or delay testing. Participants generally employed 'watch and wait' and social distancing behaviour rather than timely presentation to testing. Concern about economic loss associated with isolating after testing, and the potential for illness transmission at testing centres further prevented testing for some participants. Conclusions: In a low COVID-19 prevalence environment, individuals rely on pre-existing strategies for interpreting and managing personal illness (such as delaying help seeking if symptoms are mild), which generally conflict with public health management advice about COVID-19. In low prevalence environments therefore public health authorities must give the public a reason to test beyond considerations of personal risk, and clearly communicate the need for ongoing COVID-19 surveillance despite the low prevalence environment.